The Intelligent Built-Environment as Cyber-Physical System - Liu Cheng, Alexander (A+BE | Architecture and the Built Environment, 2024)
This thesis presents an alternative approach to intelligence in the built-environment, departing from the two established yet divergent branches in the discourse: the Technical, centered around Information and Communication Technologies (ICTs), and represented by Ambient Intelligence (AmI) and Ambient Assisted Living (AAL); and the Architectural, centered around architectural / spatial experiences and considerations, and represented by Interactive Architecture and Adaptive Architecture. The promise of both AmI/AAL and IA/AA is constrained by rigid and increasingly outdated assumptions in their approaches—i.e., AmI’s / AAL’s approach to the built-environment, and IA’s / AA’s approach to ICTs. Moreover, it is impossible to combine them to yield a cohesive system due to disparity in their typical Technology Readiness Levels. That is, the sophistication of a system depends on that of its mutually complementing subsystems; and two or more subsystems may not mutually complement, sustain, and/or support one another if their levels of development do not correspond. Consequently, the presented alternative conceives the intelligent built-environment as a Cyber- Physical System. Under this approach, ICTs and Architectural considerations in conjunction instantiate intelligence fundamentally. The presented approach’s promise is illustrated via its application to a constrained use-case focused on the elderly. Twelve proof-of-concept demonstrators are developed based on key parameters pertaining to Indoor Environmental Quality and Quality of Life. While each demonstrator is presented as a discrete proof-of-concept, all build on the same core System Architecture and technological ecosystem, and are intended to be viewed as a collection of systems and services expressed within a same hypothetical environment.